Eve - Young, William P. (Howard Books, an imprint of Simon & Schuster, Inc., 2015)
"The Shack shattered our limited perceptions about God. Eve will destroy harmful misconceptions about ourselves. From the author of the 25-million copy bestseller The Shack comes a captivating new novel destined to be one of the most important and talked-about books of the decade. When a shipping container washes ashore on an island between our world and the next, John the Collector finds a young woman inside--broken, frozen, and barely alive. With the aid of Healers and Scholars, John oversees her recovery and soon discovers her genetic code connects her to every known human race. She is a girl of prophecy and no one can guess what her survival will mean... No one but Eve, Mother of the Living, who calls her "daughter," and invites her to witness the truth about her story--indeed, the truth about us all. Eve is a bold, unprecedented exploration of the Creation narrative, true to the original texts and centuries of scholarship--yet with breathtaking discoveries that challenge traditional misconceptions about who we are and how we're made. As The Shack awakened readers to a personal, non-religious understanding of God, Eve will free us from faulty interpretations that have corrupted human relationships since the Garden of Eden. Eve opens a refreshing conversation about the equality of men and women within the context of our beginnings, helping us see each other as our Creator does--complete, unique, and not constrained to cultural rules or limitations. Thoroughly researched and exquisitely written, Eve is a masterpiece that will inspire readers for generations to come"--